Brine Treatment to Recover More Seawater by Numerical Solutions - Zacchei, Enrico; Nogueira, Caio Gorla [UNESP] (Springer Nature, 2024)
With the growing world population and industrial production, the demand for water has been continuously increasing. By 2030, ~60.0% of the world population will not have access to freshwater since it represents only ~2.50% of the total global water. For this, more of 17000 desalination plants have been constructed worldwide to recover more freshwater. However, this process, with a 50.0% efficiency, also produces brine. Brine is a liquid waste with high concentrations of salinity, which, if discharged directly into the sea, produces disastrous consequences for the environment and marine species.In this paper, advanced numerical analyses for brine treatments have been carried out. They consist in combining the transport of ions, electroosmotic mass flux, and electrochemical mechanisms in a brine-clay-seawater model. Results have been plotted in terms of ion concentrations and tank sizes.
Keywords: Brine; Desalination; Electrochemicalmechanisms; electroosmotic mass flux; transport of ions